Utilization of Chitosan as an Animal Feed Supplement and Its Effect on Fattening of Indigenous Chicken - Nur Hakiki; Suherman Suherman; Paulus H Abram (Jurnal Akademika Kimia, 2019)
Feeding types to chickens influence on the fattening speed. The purpose of this study is to determine the influence of chitosan in the mixture of chicken feed on fattening of indigenous chickens. This study applied chicken feed as a mixture of corn and chitosan in various concentration of 0%, 2%, 4%, 6%, 8%, and 10% it was given on the morning, afternoon and early evening. The results showed that the weight of chickens fed only with animal feed and without the addition of chitosan is smaller than that of chicken fed with the addition of chitosan. The use of chitosan in livestock feed influence on the chicken weight gain in 1 week by 0.1 kg.